2003
DOI: 10.1152/japplphysiol.00221.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spleen volume and blood flow response to repeated breath-hold apneas

Abstract: The purpose of this study was 1) to answer whether the reduction in spleen size in breath-hold apnea is an active contraction or a passive collapse secondary to reduced splenic arterial blood flow and 2) to monitor the spleen response to repeated breath-hold apneas. Ten trained apnea divers and 10 intact and 7 splenectomized untrained persons repeated five maximal apneas (A1-A5) with face immersion in cold water, with 2 min interposed between successive attempts. Ultrasonic monitoring of the spleen and noninva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
148
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(173 citation statements)
references
References 19 publications
20
148
5
Order By: Relevance
“…Interestingly, apnea in splenectomized subjects was found not to induce a Hb increase [5], and neonates with asplenia showed impaired transient elevation of blood Hb in response to acute hypoxia [8]. Bakovic and associates concluded that the contraction is an active process, as no differences in blood flow in the splenic artery or vein occurred [9], and total plasma protein levels remained unchanged across apnea series ruling out extravasation of plasma [5].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, apnea in splenectomized subjects was found not to induce a Hb increase [5], and neonates with asplenia showed impaired transient elevation of blood Hb in response to acute hypoxia [8]. Bakovic and associates concluded that the contraction is an active process, as no differences in blood flow in the splenic artery or vein occurred [9], and total plasma protein levels remained unchanged across apnea series ruling out extravasation of plasma [5].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that voluntary breath-hold triggers splenic contraction [6,7]. Our aim was to test the hypothesis that voluntary breathholds are also associated with an increase in MPV.…”
mentioning
confidence: 94%
“…In contrast, they did not observe significant variations in the values of erythrocyte indices, such as MCH, MCV and MCHC (LOMBARDI et al 2011). Also BAKOVIC et al (2003) demonstrated that immersion in water (12°C) results in an increase in erythrocyte, leukocyte and thrombocyte counts, and interpreted this phenomenon as an adaptation to exercise performed in cold water. LUKASKI et al (1990) did not document significant changes in the concentration of hemoglobin and hematocrit level of winter swimmers, but observed an increase in the level of iron metabolism marker, ferritin.…”
Section: Discussionmentioning
confidence: 93%